Through the looking-glass and what Alice found there - Carroll, Lewis, 1832-1898.; Tenniel, Sir John (London : Macmillan, 1968)
In this sequel to "Alice in Wonderland" Alice goes through the mirror to find a strange world where curious adventures await her.
Keywords: Alice -- (Fictitious character from Carroll) -- Fiction; Fantasy; Fantasy fiction